Preclinical Safety Evaluation of Human Mesenchymal Stem Cell Transplantation in Cerebrum of Nonhuman Primates. (September 2014) - Feng, Ming; Li, Yan; Han, Qin; Bao, Xinjie; Yang, Ming; Zhu, Hua; Li, Qin; Wei, Junji; Ma, Wenbin; Gao, Hong; An, Yihua; Zhao, Robert Chunhua; et al.
The efficacy of stem cell transplantation for promoting recovery of patients with neurological diseases, such as stroke, has been reported in several studies. However, the safety of the intracerebral transplantation of human mesenchymal stem cells (hMSCs) remains unclear. The aim of the study was to evaluate the safety of hMSCs transplanted in cerebrum of Macaca fascicularis and to provide evidence for clinical application. A total of 24 M fascicularis were assigned to 3 groups randomly: low dose (3.0 × 10 5 cells/kg), high dose (2.5 × 10 6 cells/kg), and the control (normal saline [NS]). Human mesenchymal stem cells or NS were injected into each monkey for 2 times, with an interval of 3 weeks. The injection point was located outside of the right putamen, according to a stereotactic map and preoperative magnetic resonance imaging of the monkeys. Animal health, behavior, biophysical and biochemical parameters, and brain neurological function were routinely monitored over a 6-month period posttransplantation, and the histopathologic examinations were also performed. The results showed that local pathologic damage including local tissue necrosis and inflammation was induced after the injection. The damage of low-dose and high-dose groups was greater than that of the control group, yet over time, the damage could be repaired gradually. No major hMSCs-associated changes were induced from other indicators, and the transplantation of hMSCs in monkeys did not affect total immunoglobulin (Ig) M, total IgG, CD3, CD4, or CD8 values. We therefore conclude that transplantation of hMSCs to the cerebrum represents a safe alternative for clinical application of neurological disorders.